Nodular anterior scleritis in systemic sclerosis: a case report - Komang Putra Tridiyoga; Ida Ayu Ary Pramita; I Gusti Ayu Made Juliari; A. A Mas Putrawati Triningrat; I Made Agus Kusumadjaja; N.K Niti Susila (Intisari Sains Medis, 2021)
Introduction: Scleritis is an inflammation of the sclera’s lining, characterized by cellular infiltration, collagen damage, and vascular changes. The incidence rate of scleritis accompanied by systemic disease generally is around 39% to 50%. Scleritis can be divided into two, namely anterior and posterior scleritis. Anterior scleritis can be divided into four, diffuse anterior scleritis, nodular anterior scleritis, necrotizing anterior scleritis with inflammation and without inflammation. One of the causes of nodular anterior scleritis is systemic sclerosis which is an autoimmune disease. Nodular anterior scleritis in systemic sclerosis is very rare, with an estimated prevalence rate of 4.4%.Case Description: A man, 46 years old, complaining of red, watery, painful, and visible white membrane on his right eye since two weeks ago and was referred from an ophthalmologist with scleritis on his right eye. The patient had a history of asthma and cataract surgery. Physical examination showed right eye VA was 6/45 pinhole (PH) 6/18, conjunctival and scleral injection, nodule on superior conjunctiva with yellowish-white in color. Laboratory examination showed a clinical representation of autoimmune disease, consulted to the rheumatology division, and was diagnosed with systemic sclerosis. The patient has been prescribed corticosteroids and immunosuppressant’s for the therapy, the patient's eye condition improves after.Conclusion: Systemic sclerosis with a presenting ophthalmologic complaint is a rare disease. This case illustrates that nodular anterior scleritis needs comprehensive intervention to seek the etiology and provide the treatment. This case has shown that nodular anterior scleritis with systemic sclerosis improved with corticosteroids and immunosuppressants, a typical treatment for autoimmune disease.